Hydrogen Storage Stability of Nanoconfined MgH2 upon Cycling - Huen, P.; Paskevicius, Mark; Richter, B.; Ravnsbaek, D.; Jensen, T. (MDPI AG, 2017)
It is of utmost importance to optimise and stabilise hydrogen storage capacity during multiple cycles of hydrogen release and uptake to realise a hydrogen-based energy system. Here, the direct solvent-based synthesis of magnesium hydride, MgH2, from dibutyl magnesium, MgBu2, in four different carbon aerogels with different porosities, i.e., pore sizes, 15 < Davg < 26 nm, surface area 800 < SBET < 2100 m2/g, and total pore volume, 1.3 < Vtot < 2.5 cm3/g, is investigated. Three independent infiltrations of MgBu2, each with three individual hydrogenations, are conducted for each scaffold. The volumetric and gravimetric loading of MgH2 is in the range 17 to 20 vol % and 24 to 40 wt %, which is only slightly larger as compared to the first infiltration assigned to the large difference in molar volume of MgH2 and MgBu2. Despite the rigorous infiltration and sample preparation techniques, particular issues are highlighted relating to the presence of unwanted gaseous by-products, Mg/MgH2 containment within the scaffold, and the purity of the carbon aerogel scaffold. The results presented provide a research path for future researchers to improve the nanoconfinement process for hydrogen storage applications